2017
DOI: 10.22336/rjo.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma after penetrating keratoplasty

Abstract: Penetrating keratoplasty is a surgical intervention that despite the progress of surgical techniques and of postoperative treatment continues to have numerous complications. Many of them, such as graft rejection, significant astigmatism, cystoid macular edema, or cataract lead to important limitations of the visual function. Glaucoma is possibly the most dangerous complication following PK, leading to loss of the visual potential of the eye due to irreversible damage to the optic nerve. Identifying the risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
18
0
5
Order By: Relevance
“…In the case of retained host's Descemet's membrane, severe corneal edema increases the risk of incomplete trephination and removal of the cornea at the stroma, just anterior to Descemet's membrane. 6 PAS-staining of our excised membrane confirmed presence of Descemet's membrane ( Figue 2a, c ) , and OCT of the intact membrane demonstrates traction on the lip of host cornea ( Fig. 1 c and d).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the case of retained host's Descemet's membrane, severe corneal edema increases the risk of incomplete trephination and removal of the cornea at the stroma, just anterior to Descemet's membrane. 6 PAS-staining of our excised membrane confirmed presence of Descemet's membrane ( Figue 2a, c ) , and OCT of the intact membrane demonstrates traction on the lip of host cornea ( Fig. 1 c and d).…”
Section: Discussionmentioning
confidence: 61%
“…Recommendations for removal include either surgical excision with 23 Ga or 25 Ga retinal forceps and scissors or Nd:YAG laser to open the membrane and restore normal aqueous flow and clear the central visual axis. 6 In a similar case of corneal decompensation following placement of two shunt devices complicated by fibrous ingrowth with horizontal Descemet's membrane traction, Shazly et al utilized real-time intraoperative OCT to perform Descemet stripping automated endothelial keratoplasty (DSAEK) and removal of fibrous membrane, providing distinct dissection planes of the membrane in the setting of corneal opacification. 7 In our case of fibrous membrane extending from posterior cornea to iris, the poor view of the peripheral anterior chamber secondary to recent corneal transplantation was aided by the use of intraoperative OCT, especially in the manipulation and acquisition of material for biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In corneal transplantation, AS-OCT provides images of the host-graft junction and of retrocorneal membranes [13]. In endothelial keratoplasty, AS-OCT can visualize and monitor the graft attachment.…”
Section: Ultrasound Biomicroscopy (Ubm)mentioning
confidence: 99%
“…It can range between 9% and 35%, during the early and late postoperative phase. 3,4 Certain conditions are considered as important risk factors for PKG, such as; a previous history of glaucoma, a failed keratoplasty, a history of perforation, aphakic bullous keratopathy, combining PK with cataract extraction, steroid use and iridocorneal synechiae 3. A study done by Stewart et al showed a higher incidence of PKG among patients with Pseudophakic/Aphakic Bullous keratopathy in comparison to those with keratoconus and Fuch's dystrophy with an incidence of 41% to 18% respectively, whereas diseases such as keratoconus and corneal dystrophy were seen as low risk.…”
Section: Introductionmentioning
confidence: 99%
“…6 The diagnosis of PKG represents a challenge to ophthalmologists due to variation in the IOP reading during the early postoperative period caused by the changes in the thickness of the cornea or presence of scars or from corneal distortion. 3,4 Glaucoma following keratoplasty can be defined as an increase in the intraocular pressure (IOP) above 21mmHG with or without associated alternation in vision or optic nerve modifications keratoplasty (ocular hypertension and glaucoma can be used interchangeably in this case) 7,8 and that necessitates treatment. This study will tackle the different indications of penetrating keratoplasty in the Lebanese population and will highlight the rate of post-op Glaucoma and the probable predisposing risk factors and treatment's outcome.…”
Section: Introductionmentioning
confidence: 99%